Anode structure and preparation method thereof
By adopting a multi-layer film design in the top-emitting OLED microdisplay device, including aluminum, copper and transition metal nitride layers, the problem of insufficient reflectivity and work function of the anode material in the prior art is solved, and low turn-on voltage and high turn-off voltage are achieved The effect of luminous efficiency.
Patent Information
- Application Number
- CN201910509975.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-06-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2039-06-13
AI Technical Summary
The prior art is difficult to realize high reflectivity, high work function and low cost anode materials in top-emitting OLED microdisplay devices, resulting in problems of high turn-on voltage and low luminous efficiency.
Using a multi-layer film design, including an aluminum layer as a reflection enhancement layer, a copper layer as a diffusion barrier layer and a transition metal nitride layer as a matching layer, it is prepared by magnetron sputtering and pulsed laser deposition technology to improve the reflectivity and work function of the anode. , while reducing resistance.
It effectively reduces the turn-on voltage of the top-emitting OLED microdisplay device, improves the luminous efficiency, and meets the requirements of high reflection, high work function and low resistance.
Smart Images

Figure CN112086574B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to semiconductor technology, and in particular to an anode structure and a preparation method thereof. Background Art
[0002] Organic Light-Emitting Devices (OLED) are optoelectronic products that have been widely studied since the development of flat panel displays and solid-state lighting technologies. Compared with traditional bottom-emitting devices, top-emitting devices can achieve high-quality display on Si-based or active-driven TFT substrates with complex circuit systems, which caters to the current needs of high-resolution, large-size and full-color display, and is the focus of current OLED research. Since the silicon-based chip substrate is opaque, the light-emitting unit of the OLED microdisplay must be designed as a top-emitting structure, which makes top-emitting OLED (TEOLED) an important topic in the design of OLED microdisplays. In order to consider the need for integration with silicon-based circuits, the selectivity of light emission due to the strong microcavity effect in the top-emitting structure, as well as the technical difficulties such as the preparation of transparent top electrodes and device packaging, the design and manufacture of low-driving voltage, high-brightness top-emitting OLEDs are very challenging, which also leads to the technical difficulty of OLED microdisplays.
[0003] Combined with the integration requirements of silicon-based circuits, to make an efficient silicon-based OLED micro-display top-emitting device and realize commercialization, the following series of conditions must be met: 1. Low turn-on voltage to meet the requirements of ordinary CMOS devices; 2. The lower electrode must have a high reflectivity to achieve the selectivity of light emission due to the strong microcavity effect in the top-emitting structure; 3. A semi-transparent cathode (upper electrode) with good stability and high transmittance; 4. The work function of the anode material is relatively high, which reduces the hole injection barrier and improves the turn-on voltage to achieve low-voltage driving; 5. Device packaging; 6. Simple process and high yield rate. Therefore, the design and preparation of low-driving voltage and high-brightness TEOLEDs are very challenging, which also brings great difficulties to the design of OLED micro-displays; another more important point is that product commercialization must face the requirements of product qualification rate and cost, and the process must be simple and efficient at the same time.
[0004] In OLED devices, the hole injection layer is adjacent to the metal lower electrode. At present, the highest occupied molecular orbital (HOMO level) of typical organic hole injection materials HIL is greater than 5.0eV. In order to improve the efficiency of hole injection and reduce the turn-on voltage, the selection of the metal lower electrode is crucial, especially its work function must be able to match the HOMO of the HIL layer. Therefore, the work function of the metal material must be studied and carefully selected, so high work function metals become the first choice. In addition, the typical distance between the upper and lower electrodes, that is, the film thickness of the OLED organic material, is generally in the order of hundreds of nanometers, which is in the visible light wavelength range. The anode and cathode form a reflective surface and a semi-reflective surface, and a resonant cavity is formed between the positive and negative electrodes, resulting in a strong microcavity effect in the OLED device. Therefore, in the top-emitting device, the lower electrode is also required to have a high reflectivity to fully utilize the microcavity effect and improve the luminous efficiency of the device. It can be seen that the metal work function and reflectivity of the lower electrode are two key factors to consider for the anode of the top-emitting device.
[0005] In the top-emitting device structure, due to the absorption and reflection of the organic layer and the transparent conductive electrode itself, the light energy will suffer a great loss. How to further improve the light output is an important part of the current OLED research. The high reflectivity of the lower electrode can significantly improve the OLED luminous efficiency, so the preparation of the high-reflectivity lower electrode has always been a research hotspot. Some common metals such as Ag, Al, Au, Ni, Pt, Mo, etc. have been widely studied as device anode materials. The reflectivity of Al and Ag in the visible band is as high as 90%, but their work function is slightly lower, only about 4.3eV. The work function of Au, Ni, Pt, etc. is higher, but the reflectivity is only about 50%. In 2004, the Kwok research group used Pt as a reflective anode and Pr2O3 as a hole injection layer to prepare a top-emitting device, and the device performance was close to that of a traditional bottom-emitting device. In 2004, Chen et al. prepared an inverted top-emitting device using Al and Ag as reflective cathodes, a three-layer thin film structure of Alq3 / LiF / Al as an electron injection layer, and Ag as a semi-transparent anode. With Alq3 as the light-emitting layer, the device current efficiency was 5.3cd / A (Ag cathode) and 4.5cd / A (Al cathode). Therefore, to improve the light extraction efficiency of OLEDs, reflectivity is the key factor to consider for the anode of top-emitting devices.
[0006] At present, mature standard CMOS circuits generally operate below 5V. To combine OLED and CMOS driving circuits, the operating voltage of OLED must be reduced. Research by Adachi et al. shows that the potential barrier between the OLED anode and the hole transport layer has a great influence on the performance of the device, and even directly determines the turn-on voltage of the device. A small injection barrier can reduce the turn-on voltage of the device, thereby improving the stability and luminous efficiency of the device and increasing the life of the device. There are several common methods to improve the hole injection efficiency: 1. Use high work function anode metal; 2. Metal surface modification and pretreatment; 3. Use molecular materials with low HOMO values as hole injection layers between the anode and the hole transport layer.
[0007] The research on the anode of top-emitting OLED devices at home and abroad focuses on using "interface engineering" to reduce surface roughness and using metals with high work functions to reduce driving voltage. For example, scholars such as Marks from Northwestern University in the United States used self-assembly technology to organically functionalize the surface of ITO to increase hole injection; Shen et al. found that the surface flatness of the ITO electrode can be improved after the ITO electrode is modified with Pt, and compared the EL performance of the two devices with and without Pt modification. It was found that the injection efficiency of holes from the ITO electrode can be effectively improved after the ITO electrode is modified with Pt, which is nearly 2 orders of magnitude higher than before. Patents such as Samsung SDI and Innolux Corporation (US2005 / 0224789A1, US007417261B2 and US007109652B2) of South Korea have announced the anode of top-emitting OLED devices with a two-layer structure design. The first layer of the anode structure uses a high-reflectivity metal material, and the second layer uses a transparent conductive oxide material. Among them, in order to effectively inhibit the corrosion of the metal click interface by electrochemical reaction, Samsung's patent also discloses a method of preparing a layer of metal silicide at the interface to improve the stability of the anode interface. Although various solutions (CN 101345292B, CN103219472B, CN107331786A) have also improved the anode characteristics to a certain extent, so far, the anode materials with high reflectivity, high work function and low cost have not been well solved. Summary of the invention
[0008] The technical problem to be solved by the embodiments of the present invention is to provide an anode structure of a top-emitting OLED micro-display device with high reflectivity, high work function and low resistance based on the above-mentioned existing technology.
[0009] In order to solve the above technical problems, the technical solutions provided by the embodiments of the present invention are as follows:.
[0010] An anode structure is applied to a top-emitting OLED microdisplay device, and comprises, on a Si substrate, from bottom to top: a first reflection enhancing layer, used to enhance the reflectivity of the anode structure; a second diffusion barrier layer, used to block the diffusion of the first reflection enhancing layer; and a third matching layer, used to match the highest occupied molecular orbital of a hole injection layer.
[0011] Preferably, in the above-mentioned anode structure, the first reflection enhancing layer is an Al layer; the second diffusion barrier layer is a Cu layer; and the third matching layer is a transition metal nitride layer.
[0012] Preferably, in the above-mentioned anode structure, the thickness of the Al layer is between 100 and 120 nm; the thickness of the Cu layer is between 5 and 10 nm; and the thickness of the transition metal nitride layer is between 3 and 8 nm.
[0013] Preferably, in the above-mentioned anode structure, the transition metal nitride comprises: binary compounds ZrN and HfN, ternary compounds ZrxHf1-xN, TixZr1-xN, HfxZr1-xN and TixHf1-xN; wherein 0 <x<0.15。
[0014] The present invention also discloses a method for preparing an anode structure, which is used for preparing the above-mentioned anode structure, including: preparing the first reflection enhancement layer by magnetron sputtering deposition; and preparing the second diffusion barrier layer and the third matching layer by pulsed laser deposition.
[0015] Preferably, in the above-mentioned method for preparing the anode structure, when the first reflection enhancing layer is an Al layer, the preparation of the first reflection enhancing layer by magnetron sputtering deposition includes: depositing an Al target on a Si substrate by magnetron sputtering; the deposition temperature is room temperature, and the growth atmosphere is argon.
[0016] Preferably, in the above-mentioned method for preparing the anode structure, when the second diffusion barrier layer is a Cu layer, the preparing the second diffusion barrier layer by pulsed laser deposition includes: in a vacuum atmosphere, by pulsed laser deposition, laser ablating a Cu target to prepare the Cu layer on the Al layer.
[0017] Preferably, in the above-mentioned method for preparing the anode structure, when the third matching layer is a transition metal nitride layer, and the transition metal nitride includes: binary compounds ZrN and HfN, ternary compounds ZrxHf1-xN, TixZr1-xN, HfxZr1-xN and TixHf1-xN, the preparation of the third matching layer by pulsed laser deposition includes: in a nitrogen atmosphere, by pulsed laser deposition, laser ablation of ZrN (Zr) target or HfN (Hf) target to prepare a ZrN layer or HfN layer on the Cu layer, and then preparing a binary transition metal nitride layer ZrN or HfN thin film.
[0018] Preferably, in the above-mentioned method for preparing the anode structure, the preparation of the third matching layer by pulsed laser deposition also includes: in a nitrogen atmosphere, by pulsed laser deposition, laser ablation of ZrHf9 target, Zr9Ti target, Zr9Hf target and Hf9Ti target deposition, to prepare the ternary transition metal nitride layers ZrxHf1-xN, TixZr1-xN, HfxZr1-xN and TixHf1-xN.
[0019] Preferably, in the above-mentioned method for preparing the anode structure, the laser wavelength used in the pulsed laser deposition method is 248 nm, the laser pulse width is 25 ns, and the maximum pulse repetition frequency is 10 Hz.
[0020] The present invention adopts a multilayer film design to improve the performance of the anode, wherein a reflection enhancing layer, such as an Al layer, is used to improve the reflectivity of the anode, a diffusion barrier layer, such as a Cu layer, is used to block the diffusion of Al, and a matching layer, such as a transition metal nitride layer, has a high work function and can be used to match the HOMO energy level (highest occupied molecular orbital) of the hole injection layer. At the same time, since Al, Cu and transition metal nitrides have good electrical conductivity, the anode structure of the present invention meets the requirements of the OLED microdisplay device for high anode reflectivity, high work function and low resistance, and can effectively reduce the turn-on voltage of the top-emitting OLED microdisplay device. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of a micro-display anode structure of a top-emitting OLED device according to an embodiment of the present invention;
[0022] Figure 2 It is a schematic flow chart of a method for preparing an anode structure in an embodiment of the present invention. DETAILED DESCRIPTION
[0023] So far, the existing top-emitting OLED device anode materials still fail to achieve high reflectivity, high work function and low cost. Based on this, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.
[0024] The present invention adopts a multilayer film design to improve the performance of the anode, wherein a reflection enhancing layer, such as an Al layer, is used to improve the reflectivity of the anode, a diffusion barrier layer, such as a Cu layer, is used to block the diffusion of Al, and a matching layer, such as a transition metal nitride layer, has a high work function and can be used to match the HOMO energy level (highest occupied molecular orbital) of the hole injection layer. At the same time, since Al, Cu and transition metal nitrides have good electrical conductivity, the anode structure of the present invention meets the requirements of the OLED microdisplay device for high anode reflectivity, high work function and low resistance, and can effectively reduce the turn-on voltage of the top-emitting OLED microdisplay device.
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0026] Example 1
[0027] The anode structure of the top-emitting OLED device micro-display of the present invention can be used to improve the reflectivity of the top-emitting OLED device micro-display, such as Figure 1 As shown, on a silicon (Si) substrate, from bottom to top, an aluminum (Al) layer, a copper (Cu) layer and a transition metal nitride layer are included.
[0028] In a specific implementation, the transition metal nitride includes: binary compounds ZrN and HfN, ternary compounds ZrxHf1-xN, TixZr1-xN, HfxZr1-xN and TixHf1-xN; wherein 0 <x<0.15。
[0029] In a specific implementation, the Al layer is deposited on the cleaned Si-based substrate by magnetron sputtering, and its thickness is 100-120nm; further, the Cu layer and the transition metal nitride layer can be deposited on the Al layer successively by pulsed laser deposition, and their thicknesses are 5-10nm and 3-8nm respectively.
[0030] Example 2
[0031] The present invention also discloses a method for preparing an anode structure, which is used for preparing the anode structure in Example 1. Figure 2 As shown, the method for preparing the anode structure may include the following steps:
[0032] Step S101 , preparing a first Al layer by magnetron sputtering deposition.
[0033] The anode structure of the top-emitting OLED device microdisplay uses a silicon substrate. In a specific implementation, first, acetone, ethanol, and deionized water are used to ultrasonically clean the silicon substrate for 5 minutes.
[0034] After cleaning, it was dried with N2 and placed in a magnetron sputtering system. Al film was deposited by sputtering Al target at room temperature in Ar atmosphere with a deposition thickness of 115 nm.
[0035] Step S102 , preparing a second Cu layer by pulsed laser deposition.
[0036] In the specific implementation, the deposited sample is placed in a pulsed laser deposition system, and the substrate is heated. After reaching 400°C, the distance between the target and the substrate is adjusted to 7cm, and the pulsed laser energy is set to 350mJ and the frequency is set to 2Hz. The laser is turned on in a vacuum environment to sputter the Cu target, and the growth time is 12 minutes. After the deposition is completed, annealing is performed for 1 hour.
[0037] In the above specific implementation, the laser wavelength used in the pulse laser deposition method is 248 nm, the laser pulse width is 25 ns, and the maximum pulse repetition frequency is 10 Hz.
[0038] Step S103 , preparing a third transition metal nitride layer by pulsed laser deposition.
[0039] In a nitrogen atmosphere, a ZrN (Zr) target or a HfN (Hf) target is laser ablated by pulsed laser deposition to prepare a ZrN layer or a HfN layer on the Cu layer, thereby preparing a binary transition metal nitride layer ZrN or HfN thin film. Then, in a nitrogen atmosphere, a ZrHf9 target, a Zr9Ti target, a Zr9Hf target and a Hf9Ti target are laser ablated by pulsed laser deposition to prepare the ternary transition metal nitride layers ZrxHf1-xN, TixZr1-xN, HfxZr1-xN and TixHf1-xN.
[0040] The growth temperature of the binary transition metal nitride layer and the ternary transition metal nitride layer is 300-500° C., the growth environment is a nitrogen atmosphere with a pressure of 1-3 Pa, and in-situ annealing is performed for 1 hour after the growth is completed.
[0041] In a specific implementation, after the Cu layer deposition in step S102 is completed, nitrogen is introduced into the epitaxial growth chamber of the pulse laser deposition system through the gas pipeline, and the pressure is adjusted to 3 Pa, the distance between the target and the substrate is adjusted to 7 cm, the pulse laser energy is set to 350 mJ, and the frequency is set to 2 Hz. The laser is turned on to ablate the ZrN film and start the deposition of the ZrN film. The growth time is 10 minutes.
[0042] After the ZrN growth is completed, in-situ annealing is performed at a temperature of 400° C. and a nitrogen pressure of 3 Pa for 1 hour, thereby completing the preparation of the anode structure.
[0043] In the above specific implementation, the laser wavelength used in the pulse laser deposition method is 248 nm, the laser pulse width is 25 ns, and the maximum pulse repetition frequency is 10 Hz.
[0044] In summary, the anode structure of the present invention meets the requirements of the OLED microdisplay device for high anode reflectivity, high work function and low resistance, and can effectively reduce the turn-on voltage of the top-emitting OLED microdisplay device.
[0045] The above is only a specific implementation of the present invention. For those skilled in the art, improvements made without departing from the principles of the present invention should be deemed to fall within the scope of protection of the present invention. It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it accordingly, and cannot be used to limit the scope of protection of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. An anode structure, applied to a top-emitting OLED micro-display device, characterized in that: On the Si substrate, from bottom to top, it includes: A first reflection enhancing layer, which is an Al layer and is used to enhance the reflectivity of the anode structure; A second diffusion barrier layer, which is a Cu layer and is used to block the diffusion of the first reflection enhancing layer; and The third matching layer is a transition metal nitride layer, which is used to match the highest occupied molecular orbital of the hole injection layer. The transition metal nitride includes: binary compounds ZrN and HfN, ternary compounds Zr x Hf 1-x N、Ti x Zr 1-x N、Hf x Zr 1-x N and Ti x Hf 1-x N, where 0 <x<0 .15。 2. The anode structure according to claim 1, characterized in that: The thickness of the Al layer is between 100 and 120 nm; The thickness of the Cu layer is between 5 and 10 nm; The thickness of the transition metal nitride layer is between 3 nm and 8 nm.
3. A method for preparing an anode structure, characterized in that: For preparing the anode structure according to claim 1 or 2, comprising: The first reflection enhancing layer is prepared by magnetron sputtering deposition; and, The second diffusion barrier layer and the third matching layer are prepared by pulsed laser deposition.
4. The method for preparing an anode structure according to claim 3, characterized in that: The step of preparing the first reflection enhancing layer by magnetron sputtering deposition comprises: The Al target was deposited on the Si substrate by magnetron sputtering; the deposition temperature was room temperature and the growth atmosphere was argon.
5. The method for preparing an anode structure according to claim 4, characterized in that: The step of preparing the second diffusion barrier layer by pulsed laser deposition comprises: The Cu layer is prepared on the Al layer by laser ablation of a Cu target in a vacuum atmosphere through pulsed laser deposition.
6. The method for preparing an anode structure according to claim 5, characterized in that: The step of preparing the third matching layer by pulsed laser deposition comprises: In a nitrogen atmosphere, a ZrN (Zr) target or a HfN (Hf) target is laser ablated by pulsed laser deposition to prepare a ZrN layer or a HfN layer on the Cu layer, thereby preparing a binary transition metal nitride layer ZrN or HfN film.
7. The method for preparing an anode structure according to claim 6, characterized in that: The step of preparing the third matching layer by pulsed laser deposition further comprises: In a nitrogen atmosphere, the ternary transition metal nitride layer Zr is prepared by laser ablation of ZrHf9 target, Zr9Ti target, Zr9Hf target and Hf9Ti target deposition through pulsed laser deposition. x Hf 1-x N、Ti x Zr 1-x N、Hf x Zr 1-x N and Ti x Hf 1-x N.
8. The method for preparing an anode structure according to claim 5, 6 or 7, characterized in that: The pulse laser deposition method uses a laser wavelength of 248 nm, a laser pulse width of 25 ns, and a maximum pulse repetition frequency of 10 Hz.
